Correlation of ankle eversion to inversion strength ratio and static balance in dominant and non-dominant limbs of basketball players - Dabadghav, R. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: To compare ankle eversion to inversion strength ratio (E/I R) and static balance control between the dominant and non-dominant limbs of basketball players and to correlate ankle E/I R and static balance control in the dominant and non-dominant limbs of basketball players.